Chemical Analyses of Zircons in Sequential Sections: An Integrated Electron Microprobe, Backscattered Electron and Cathodoluminescense Image Investigation - HARTMANN, LÉO; VASCONCELLOS, MARCOS; ROSA, ANABELA PORTO (Pesquisas em Geociências, 1999)
The three dimensional internal structure and distribution of trace elements of zircon are clarified from the observation of backscattered electron and cathodoluminescence images of zircon plus electron microprobe quantitative determinations of U, Y and Hf. Successive (100) and (001) sections of zircon crystals were investigated in two slightly sheared postectonic Cambrian granites from southernmost Brazil. Fractures are sealed, and the chemical modifications are seen to migrate into euhedral bands and even larger volumes of the crystals – the contents of U and Hf usually increase significantly, and Y variably so. The sealing of fractures present in one section is observed to evolve to euhedral banding in the next, tying the two features to the same genetic process.